Contribution of haptoglobin phenotypic variation to the presence of hyperhomocysteinemia in type 2 diabetics with and without angiopathy - Ferreira, Isabel; Bicho, Manuel; Valente, Ana (European journal of clinical nutrition, 2025)
Background/Aim The genetic polymorphism of haptoglobin (Hp) has been associated with several cardiovascular risk factors, but a possible relationship between Hp phenotypic variation and increased levels of homocysteine (Hcy) and cysteine (Cy) is still unknown. The objective of this study is to evaluate the relationship between the Hp polymorphism and hyperhomocysteinemia (HHcy) and hypercysteinemia (HCy) in type 2 diabetics (T2D) with and without angiopathy (AGP). Methods A case-control study was carried out on 293 adults: Group I (GI) - 75 subjects with T2D and AGP; Group II (GII) - 75 subjects with T2D without AGP; Group III (GIII) - 143 controls. Plasma levels of Hcy, Cy and vitamin B 6 were measured by high performance liquid chromatography (HPLC) and vitamins B 9 and B 12 determined by electrochemiluminescence (ECL). The Hp polymorphism was identified by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE) and peroxidase staining. The results were analyzed in SPSS®, version 26.0 with a significance of 95%. Results Mean Hcy concentrations were significantly lower in carriers of the Hp2-2 phenotype (6.14 µM; p = 0.046) compared to the other genotypes. The presence of Hp2-1 is associated with an approximately 3.3 times greater probability of occurrence of HHcy ( p = 0.015) and 3.7 times greater probability occurrence of HCy ( p = 0.021) in T2D with AGP. Conclusion The presence of the Hp2-1 phenotype is associated with the predisposition of HHcy and HCy in individuals with T2D and AGP, possibly through a positive heterosis mechanism. Carriers of the Hp2-2 phenotype appear to have a greater activation of the transsulfuration pathway in the Hcy cycle and consequent protection for its accumulation.